An expression system for Gustatory receptors-and why it failed. - Amrein, H. (Fly, 2014)
A recent paper by the Dahankuar laboratory suggested that single Drosophila sugar receptors proteins accurately mediate sugar detection when ectopically expressed in olfactory neurons of the antenna. These findings contra-dict numerous previously published electrophysiological and behavioral investigations, which all point towards heteromultimeric sugar taste receptors. Here, I provide some explanation why this "pseudo-heterologous" expression system may have led to this misleading conclusion.